2018
DOI: 10.21161/mjm.110217
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of caffeine by Pseudomonas monteilii KRM9

Abstract: Aims:The objective of this research was to isolate caffeine-degrading bacteria from coffee pulp waste in Indonesia and characterize their caffeine degradation activity. Methodology and results: The caffeine-degrading bacteria were isolated from coffee pulp wastes of Coffea arabica and C. canephora. These isolates were selected based on their caffeine degradation activity. The identification and biochemical properties of the best isolate were conducted via 16S rDNA sequence analyses and by using the Microbact k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Vega et al (2005) identified 19 bacterial genera as endophytes in coffee plants from Colombia, Hawai'i, and Mexico, with Bacillus, Burkholderia, Clavibacter, Curtobacterium, Escherichia, Micrococcus, Pantoea, Pseudomonas, Serratia, and Stenotrophomonas isolated from the seed. Pseudomonas sp., P. chloroaphis, and P. putida were identified as endophytes in various coffee plant tissues sampled (Vega et al, 2005) and P. monteilii has been isolated from coffee pulp waste (Arimurti et al, 2018). A coffee plant endophytic Pseudomonas sp.…”
Section: Caffeine-degrading Bacteria In Soil and Plantsmentioning
confidence: 99%
“…Vega et al (2005) identified 19 bacterial genera as endophytes in coffee plants from Colombia, Hawai'i, and Mexico, with Bacillus, Burkholderia, Clavibacter, Curtobacterium, Escherichia, Micrococcus, Pantoea, Pseudomonas, Serratia, and Stenotrophomonas isolated from the seed. Pseudomonas sp., P. chloroaphis, and P. putida were identified as endophytes in various coffee plant tissues sampled (Vega et al, 2005) and P. monteilii has been isolated from coffee pulp waste (Arimurti et al, 2018). A coffee plant endophytic Pseudomonas sp.…”
Section: Caffeine-degrading Bacteria In Soil and Plantsmentioning
confidence: 99%
“…As for bacteria with caffeine degrading potential, a coffee pulp isolate of Pseudomonas monteilii has been studied, with a maximum degradation of 99 % at 24 h; and E. coli DH5a transformed with a plasmid isolated from Brevibacterium sp., degraded caffeine up to 2 g/L, and with a high tolerance to coffee (Nayak et al, 2012;Arimurti et al, 2018). Caffeine degrading soil bacteria have also been isolated and identified, including 5 gram-negative species, namely Pseudomonas japonica (4/12), Methylobacterium populi (5/12), Raoultella ornithinolytica (1/12), Klebsiella quasipneumoniae (1/12) and Stenotrophomonas chelatiphaga (1/12) with a potential to be used in various applications that require removal of this antinutrient (Iswanto et al, 2019b).…”
Section: Caffeine Degradationmentioning
confidence: 99%
“…Chrysosporium keratinophilum Nayak et al, 2012Nayak et al, , 2013Pai et al, 2013;Arimurti et al, 2018 Gliocladium roseum…”
Section: Degradation Of Caffeinementioning
confidence: 99%
“…These microbes can utilize caffeine as a source of carbon and nitrogen and produce CO 2 and NH 3 as the final results (Nayak et al, 2012). In the process of utilization, the concentration of caffeine decrease (Arimurti et al, 2018). There are several caffeine degrading microbes i.e.…”
Section: Introductionmentioning
confidence: 99%